2021
DOI: 10.1007/s11136-020-02733-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of type 2 diabetes mellitus patients in Ramallah and al-Bireh Governorate–Palestine: a part of the Palestinian diabetes complications and control study (PDCCS)

Abstract: Purpose Type 2 diabetes mellitus (T2DM) is a considerable impact on physical health as well as on emotional and social wellbeing. This study aimed to investigate the quality of life and its associated factors among Palestinians with T2DM. Methods A cross-sectional study including 517 patients (68% female) was conducted in eleven primary health care clinics located in Ramallah and al-Bireh governorate of the West Bank. To assess socio-demographic data, risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
3
17
1
Order By: Relevance
“…among the respondents, (66.7%) are married. This finding is similar to the findings of other research such as (Tietjen et al, 2021) and (George and Premkumar, 2017), which found that most of the samples were married.…”
Section: Global Journal Of Public Health Medicine 2022 Vol 4 Issue 2 ...supporting
confidence: 91%
“…among the respondents, (66.7%) are married. This finding is similar to the findings of other research such as (Tietjen et al, 2021) and (George and Premkumar, 2017), which found that most of the samples were married.…”
Section: Global Journal Of Public Health Medicine 2022 Vol 4 Issue 2 ...supporting
confidence: 91%
“…A study in Palestine stated that almost 34% of DM patients experienced a poor life quality (Tietjen et al ., 2021). Meanwhile, several results showed that the diabetes mellitus patients in Indonesia averagely had a decrease in life quality.…”
Section: Resultsmentioning
confidence: 99%
“…Once any of these occur, costs of survival are increased, and life quality becomes affected. A study in Palestine showed that almost 34% of DM patients experienced a poor life quality (Tietjen et al, 2021). Meanwhile, several sources reported that DM patients in Indonesia averagely had a decrease in life quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the prevalence of diabetes is gradually increasing and is estimated to reach approximately 783 million by 2045 [ 3 ]. Furthermore, 28.6% of patients with type 2 diabetes have macrovascular complications, such as cardiovascular disease and peripheral arterial disease, and 67.2% have microvascular complications, such as retinopathy, nephropathy, and neuropathy [ 4 ]. Among them, diabetic kidney disease (DKD) is a serious diabetes-related complication and is the most important cause of end-stage renal failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%